An Analysis of English Textbook Entitled "Bahasa Inggris SMA/MA SMK/MAK Kelas X": Analisis Buku Ajar Bahasa Inggris Berjudul "Bahasa Inggris SMA/MA SMK/MAK Kelas X" - Tyas, Peptia Asrining; Safitri, Mega (JEES (Journal of English Educators Society), 2019)
A textbook plays an important factor in teaching and learning processes. Thus, this study attempted to analyze an English textbook entitled Bahasa Inggris Bahasa Inggris SMA/MA SMK/MAK Kelas X which is used by almost teachers in secondary level education. This study used qualitative study by using Biocchi’s (2000) coursebook evaluation and interview which was adopted open-ended questions from Biocchi’s (2000) coursebook evaluation. The analysis encircled the contents, grammar, levels of the material, kind of the materials, and the methodology used in the textbook. The results revealed that this textbook was well designed and encouraged students’ autonomy to learn and use the language. Besides, this textbook achieved Biocchi’s (2000) coursebook evaluation (contents, grammar focus, level, material, and methodology) well. Although this book is good enough, there is a weakness; it is not provided by CD for listening activity, so the teachers have to find and create their own audio.